VIETNAM - RUSSIAN COOPERATION INSTALLING AND TESTING THE TOMOGRAPHY ELECTRIC COMPLEX (TEC-2) FOR INVESTIGATION OF SHALLOW GEOLOGICAL ENVIRONMENT - Cuong, Do Huy; Anh, Bui Thi Bao; Nhan, Nguyen Thi; Tung, Nguyen Xuan; Hung, Pham Duc; Thanh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2015)
The geophysical investigation system named TEC-2 (Tomography Electric Complex-2) was designed, installed and tested in Institute of Marine Geology and Geophysics. This TEC-2 is the scientific cooperation product of Geomagnetic and Geoelectric Department of and POI and Geo - environmental Department of IMGG-VAST. The test results using TEC-2 show the capability of investigating by using certain pole system, short investigation time, high stability, the accuracy of two investigation times being more than 92%. The distributed design of electric poles, measuring operation, parameter selection, … are programmed and controlled automatically by computer. The TEC-2 system was used for investigating the weak structures in islands of Song Tu Tay, Son Ca, Nam Yet and Sinh Ton in Truong Sa Archipelagos and shallow geological environment in the area of Red River bank in Son Tay Hanoi. The acquired data  contributed to the success of the scientific projects managed by IMGG in the National Program of Bien Dong and islands in the period of 2011 - 2013 and VAST’s research project in the period of 2013 - 2014.